Erythema Multiforme after Unilateral Adrenal Adenoma Resection in a Patient with Cushing’s Syndrome - Gu, Liping; Ding, Xiaoying; Zhen, Qin; Li, Na; Peng, Yongde; Wang, Yufan (Archives of Clinical and Medical Case Reports, 2019)
Introduction: Cushing’s syndrome is characterized by endogenously increased production of glucocorticoids. It has been postulated that excessive immune response may occur after an immediate withdrawal of high glucocorticoids after surgical therapy of Cushing’s syndrome. We reported a rare case of severe erythema multiforme after unilateral adrenal adenoma surgery for Cushing’s syndrome. Case Presentation: A 28-year-old man was incidentally found to have a left adrenal nodule at a regular physical examination 3 years ago. He suffered from increased appetite, gained body weight (2 years increased by 20 kg) and fracture of multiple ribs. Endocrinological examinations showed autonomous secretion of cortisol and suppression of plasma ACTH level. Imaging examination revealed a left adrenal gland adenoma. He was diagnosed with ACTH-independent Cushing’s syndrome due to left adrenal adenoma. Laparoscopic resection of left adrenal adenoma was then performed. Hydrocortisone was given intravenously and tapered after operation, followed by oral prednisone replacement therapy (10 mg/day) five days later. The patient developed a systemic pruritic rash with moderate fever of 38.6°C and conjunctivitis on postoperative day 20. He was diagnosed as erythema multiforme and received a twenty-day intravenous injection of methylprednisolone, followed by oral prednisone. External application of dexamethasone was administrated simultaneously. The fever subsided on day 7 of fever onset and the skin lesions presented with massive erythema. The erythema gradually expanded to fuse and finally subside after epidermal detachment. The skin returned to normal after molting on approximately day 45. The prednisone was discontinued 6 months after the operation. Conclusion: Immediate withdrawal of high glucocorticoids after surgical therapy of Cushing’s syndrome ca